2016
DOI: 10.1111/oik.03053
|View full text |Cite
|
Sign up to set email alerts
|

Phenological asynchrony in plant–butterfly interactions associated with climate: a community‐wide perspective

Abstract: Although much information has been accumulated on the effects of climate change on particular species worldwide, research aimed at assessing how such change influences biotic interactions from a community‐wide perspective is still in its infancy. We contribute to filling in this gap by analyzing a 17‐year (1996–2012) dataset that includes records of flower‐visitation interactions between 12 butterfly species and 17 plant species in a coastal wetland area in northeastern Iberian Peninsula. We assessed the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 53 publications
(103 reference statements)
0
30
1
1
Order By: Relevance
“…; but see Donoso et al . ). We found that in addition to mean values, also variability of temperature and precipitation are important in defining species phenology, which also act as a driver of plant–pollinator interactions.…”
Section: Discussionmentioning
confidence: 97%
“…; but see Donoso et al . ). We found that in addition to mean values, also variability of temperature and precipitation are important in defining species phenology, which also act as a driver of plant–pollinator interactions.…”
Section: Discussionmentioning
confidence: 97%
“…Notable changes in the arrival dates of migratory birds [89] and advances in the first appearances of several pollinators, which could be tracking the parallel shift in the flowering times of their host-plants [90], have been reported for the Mediterranean Basin. The increase in aridity, however, may also exacerbate phenological asynchronies between plants and their pollinators, as has been recently suggested for several Mediterranean butterflies [91]. These climate-induced phenological disruptions may also have unexpected eco-evolutionary consequences, biasing sex ratios in the populations of insect species where sex is determined by time and temperature [92].…”
Section: Changes In Morphology Physiology Phenology and Growth In Amentioning
confidence: 94%
“…; Donoso et al . ). The influence of plant phenology has been assessed as one important factor structuring plant–pollinator interactions in Mediterranean high mountains (Petanidou et al .…”
Section: Impacts Of Climate Change On Reproduction and Regeneration Omentioning
confidence: 97%